Treatment Effect Heterogeneity - Jeffrey A. Smith (Institute of Labor Economics (IZA), 2022)
Knowledge of treatment effect heterogeneity or "essential heterogeneity" plays an important role in our understanding of how programs work and in the design of systems to allocate them among the eligible. This paper provides a relatively non-technical survey of the current state of the treatment effect heterogeneity enterprise within economics from both substantive and applied econometric perspectives. It also suggests directions for research on treatment effect heterogeneity going forward.
Keywords: C10; C41; 330; treatment effects; essential heterogeneity; program evaluation